Integrating modelling and smart sensors for environmental and human he alth - Reis, Stefan; Seto, Edmund; Northcross, Amanda; Quinn, Nigel W. T.; Convertino, Matteo; Jones, Rod L.; Maier, Holger R.; Schlink, Uwe; Steinle, Susanne; Vieno, Massimo; Wimberly, Michael C. (Environmental Modelling & Software, 2015)
Sensors are becoming ubiquitous in everyday life, generating data at a n unprecedented rate and scale. However, models that assess impacts of human activities on environmental and human health, have typically be en developed in contexts where data scarcity is the norm. Models are e ssential tools to understand processes, identify relationships, associ ations and causality, formalize stakeholder mental models, and to quan tify the effects of prevention and interventions. They can help to exp lain data, as well as inform the deployment and location of sensors by identifying hotspots and areas of interest where data collection may achieve the best results. We identify a paradigm shift in how the inte gration of models and sensors can contribute to harnessing ‘Big Data’ and, more importantly, make the vital step from ‘Big Data’ to ‘Big Inf ormation’. In this paper, we illustrate current developments and ident ify key research needs using human and environmental health challenges as an example.
Keywords: Big data; Environmental health; Environmental sensors; Integrated modelling; Population health